2010
DOI: 10.1124/dmd.110.034231
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Inhibitory Effect of Carbapenem Antibiotics on the Deconjugation of Valproic Acid Glucuronide

Abstract: ABSTRACT:Serum concentrations of valproic acid (VPA) are markedly decreased by coadministration of carbapenem antibiotics (CBPMs). Although inhibition of deconjugation of VPA-glucuronide (VPA-G) to VPA by CBPMs has been proposed as one of the mechanisms to account for this drug-drug interaction, little information is available on the mode of inhibition. In the present study, we characterized the enzyme involved in the deconjugation of VPA-G by using human and rat liver cytosol. It is suggested that 1) deconjug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Concomitant administration with VPA and CBPs has also been associated with an increased number of epileptic seizures and epileptic activity on EEG ( 15 ). Acylpeptide hydrolase (APEH) is the key enzyme responsible for VPA-G hydrolysis ( 49 ), and CBPs have been associated with the irreversible inhibition of APEH ( 50 ). Following the discontinuation of CBP treatment, the effect on VAP has been noted to last for several days ( 13 , 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant administration with VPA and CBPs has also been associated with an increased number of epileptic seizures and epileptic activity on EEG ( 15 ). Acylpeptide hydrolase (APEH) is the key enzyme responsible for VPA-G hydrolysis ( 49 ), and CBPs have been associated with the irreversible inhibition of APEH ( 50 ). Following the discontinuation of CBP treatment, the effect on VAP has been noted to last for several days ( 13 , 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“… 43 In the case of the MEPM–pAAP complex, this hydroxyethyl substituent – analogous to the side chain of Thr – is observed to be anchored within the S1 pocket. Since the hydroxyethyl substituent is a common structural feature of all carbapenems, its moderate size as compared to those of other β-lactams provides a plausible explanation for experiencing the DDI-effect during co-administration of VPA and not only meropenem (first clinical study reported in 1998), 50 but other carbapenems such as panipenem, 1 doripenem, 51 ertapenem, 52 biapenem 53 and imipenem 54 as well, but not in the case of any other β-lactam antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacologic interaction between carbapenems and valproic acid (VPA) and its derivatives was first described in 1997 in three patients receiving concurrent panipenem and VPA and has been documented in several pharmacokinetic and clinical studies since then. [1][2][3][4][5][6][7][8][9] The mechanism of interaction has been attributed to enzyme inhibition, which appears to occur within 24 hours of concomitant administration and recovers 7-14 days after discontinuing carbapenem therapy. 2 Although the exact mechanism remains unclear, carbapenem inhibition of VPA-glucuronide conversion to VPA, thus leading to marked reductions in VPA concentrations, continues to be the widely accepted explanation.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although the exact mechanism remains unclear, carbapenem inhibition of VPA-glucuronide conversion to VPA, thus leading to marked reductions in VPA concentrations, continues to be the widely accepted explanation. [3][4][5] For patients taking VPA to treat and prevent seizures, this interaction can lead to breakthrough seizures due to significantly decreased VPA levels. [7][8][9] This interaction is potent enough that carbapenems have been given to treat VPA overdose.…”
Section: Introductionmentioning
confidence: 99%